Increasing Inequality in Experience of Victimization During the Crime Drop: Analysing Patterns of Victimization in Scotland from 1993 to 2014-15 - McVie, Susan (The British journal of criminology, 2020)
Research on the international crime drop has predominantly focused on the nature and extent of overall crime or changes in specific crime types, but less attention has been paid to how equally the crime drop has been distributed across society. Applying a novel quasi-longitudinal approach to Scottish victimization data, this article examines changes in the prevalence, frequency and type of victimization experienced. We argue that the crime drop has resulted in an increase in inequality between those at most and least risk of being a victim of crime, especially violence. The article contributes to theoretical debates on the crime drop, crime inequality and distributive justice, and provides policy recommendations on the importance of crime reduction strategies that target repeat victimization.